Analysis of Flexibility Demand with Regional Power Grid. Issue 1 (March 2021) - Tang, Ningning; Niu, Yuguang; Zhang, Guangming; Wang, Kun
Abstract: Improving the flexibility of regional power grid is an important means to solve the problem of energy abandonment. Quantitative calculation of flexibility demand is the premise of unit transformation and optimal allocation of flexible resources. This study analyzed the definition of flexibility demand, and established the model of flexibility demand. In this paper, random variables are introduced to describe the flexibility demand, and the sequence operation theory is used to solve the model. A case study is given to verify the proposed method. The results prove that the proposed method can calculate the probability distribution of flexibility demand in the planning year without detail information of units. It can provide a reference for the capacity transformation of units and the optimal allocation of flexible resources.